Effect of Training and Development on Employee Productivity in Private Hospitals in Nyeri County, Kenya - Mualuko, Josephat; Rintari, Nancy; Moguche, Abel (Human Resource and Leadership Journal, 2023)
Purpose: To explore the effect of training and development on employee productivity in private hospitals in Nyeri County, Kenya Methodology: The study adopted descriptive research design to collect data using closed-ended questionnaires in 10 private hospitals in Nyeri County, Kenya. Ten (10) human resources managers and 79 departmental heads from the hospitals participated making a total of 89 respondents selected using census method. The collected data were analyzed quantitatively with SPSS Version 23 and the results presented descriptively using frequency, percentage and mean. Inferential statistics such as linear and multiple regression analysis were done whereas tables and explanations were used Results: The questionnaire responses on employee productivity indicated that a combined total of 58(77%) respondents were in agreement that there were employee productivity policies. Nevertheless, a combined total of 60(80%) did not agree that employees were usually very effective in reporting the duties performed at a particular time. The questionnaire responses on training indicated that a combined total of 59(79%) were in agreement that there was a culture of employee on job training in the organization. However, a combined total of 60(80%) did not agree that employees were allowed time off to enable for training and development. Further, the R-square was 0.224 hence indicating that training had a 22.4% influence on employee productivity. Unique contribution to theory, policy and practice: The study concluded that in as much as employees purported to have achieved their targets there was laxity on formally reporting on what they done. Additionally, when the staff requested to be given some time off to attend a personal training it was rejected since it would result to overburdening of other staff with more duties. The study recommends that hospital management should frequently conduct an audit on the procedures and processes required to be attained by the employee.